A novel assay revealed that ribonucleotide reductase is functionally important for interstrand DNA crosslink repair. Issue 21 (1st November 2015) - Fujii, Naoaki; Evison, Benjamin J.; Actis, Marcelo L.; Inoue, Akira
Graphical abstract: Abstract: Cells have evolved complex biochemical pathways for DNA interstrand crosslink (ICL) removal. Despite the chemotherapeutic importance of ICL repair, there have been few attempts to identify which mechanistic DNA repair inhibitor actually inhibits ICL repair. To identify such compounds, a new and robust ICL repair assay was developed using a novel plasmid that contains synthetic ICLs between a CMV promoter region that drives transcription and a luciferase reporter gene, and an SV40 origin of replication and the large T antigen ( LgT ) gene that enables self-replication in mammalian cells. In a screen against compounds that are classified as inhibitors of DNA repair or synthesis, the reporter generation was exquisitely sensitive to ribonucleotide reductase (RNR) inhibitors such as gemcitabine and clofarabine, but not to inhibitors of PARP, ATR, ATM, Chk1, and others. The effect was observed also by siRNA downregulation of RNR. Moreover, the reporter generation was also particularly sensitive to 3-AP, a non-nucleoside RNR inhibitor, but not significantly sensitive to DNA replication stressors, suggesting that the involvement of RNR in ICL repair is independent of incorporation of a nucleotide RNR inhibitor into DNA to induce replication stress. The reporter generation from a modified version of the plasmid that lacks the LgT-SV40ori motif was also adversely affected by RNR inhibitors, further indicating a role for RNR in ICL repair that is independent of DNA replication. Intriguingly, unhooking of cisplatin-ICL from nuclear DNA was significantly inhibited by low doses of gemcitabine, suggesting an unidentified functional role for RNR in the process of ICL unhooking. The assay approach could identify other molecules essential for ICLR in quantitative and flexible manner.